Insecticidal activity of silver nanoparticles synthesised from aqueous leaf extract of Eucalyptus tereticornis on horn flies - Jagadish Jagadish; G.S. Mamatha; C. Ravikumar; Jaya Nagappa Lakkundi; ShriKrishna Isloor; V.T. Shilpa; T.N.K.V. Prasad; H.M. Yathish; K. J. Ananda (Journal of Veterinary and Animal Sciences)
An insecticidal efficacy of silver nanoparticles (AgNps) synthesised from aqueous leaf extract of Eucalyptus tereticornis, was carried out against adults, larval and pupal stages of Haematobia flies. In in vitro adulticidal and larvicidal assays the mortality ranged between 30.0 to 67.0 and 5.0 to 75.0 per cent in treated groups after 24 hours at different concentrations, respectively. The inhibition of pupation ranged between 5.0 to 30.0 per cent after 24 hours by dipping method. The lethal concentration values were calculated for all the assays. The probit analysis revealed the significant (p<0.05) effect at different concentrations of AgNPs synthesised from aqueous leaf extract of E. tereticornis on adults, larvae and pupal mortality Keywords: Haematobia flies, silver nanoparticles, in vitro assays